Comprehensive Genome-Wide Identification, Characterization, and Expression Analysis of CCHC-Type Zinc Finger Gene Family in Wheat (Triticum aestivum L.) - Sun, Aolong; Li, Yongliang; He, Yang; Zou, Xiaoxiao; Chen, Fenglin; Ji, RuiZhao; You, Changqiao; Yu, Keyao; Li, You; Xiao, Wenjun; Guo, Xinhong (Frontiers in Plant Science, 2022)
The CCHC-type zinc finger proteins (CCHC-ZFPs) play versatile roles in plant growth, development and adaptation to the environment. However, little is known about the CCHC-ZFP gene family in Triticum aestivum. In the present study, we identified a total of 50 TaCCHC-ZFP genes from the 21 wheat chromosomes, which were phylogenetically classified into eight groups based on their specific motifs and gene structures. The 43 segmentally duplicated TaCCHC-ZFP genes were retrieved, which formed 36 segmental duplication gene pairs. The collinearity analyses among wheat and other eight mono/dicots revealed that no gene pairs were found between wheat and the three dicots. The promoter analyses of the TaCCHC-ZFP genes showed that 636 environmental stress-responsive and phytohormone-responsive cis-elements. The GO enrichment analysis indicated that all the TaCCHC-ZFP genes were annotated under nucleic acid binding and metal ion binding. A total of 91 miRNA binding sites were identified in 34 TaCCHC-ZFP genes according to the miRNA target analysis. Based on the public transcriptome data, the 38 TaCCHC-ZFP genes were identified as DEGs. The expression profiles of 15 TaCCHC-ZFP genes were verified by the qRT-PCR assays, and the results showed that these genes were responsive to drought or heat treatments. Our work systematically investigated the gene structures, evolutionary features, and potential functions of TaCCHC-ZFP genes. It lays a foundation for further research and application of TaCCHC-ZFP genes in genetic improvement of T. aestivum.